The Examination of the Effects of FDI on International Trade of the ASEAN Economic Community - Ky, Sereyvath (Journal of Ecohumanism, 2025)
The examination of the effects of foreign direct investment on international trade and trade balance was conducted within the member states of the ASEAN Economic Community, which include Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, and Vietnam, covering the period from 2001 to 2022. To derive empirical insights, various static panel data models were employed, specifically the Pooled Ordinary Least Squares, Fixed Effect, and Random Effect models. In addition to FDI, the analysis incorporated three key variables: the real GDP growth rate, inflation rate, and foreign exchange rate, to evaluate their influence on international trade. The findings of this research indicate a positive correlation between net FDI inflows and trade levels, suggesting that increased FDI contributes to enhanced trade activity. Furthermore, the results emphasize that a rise in the real GDP growth rate and a depreciation of the exchange rate can foster a favorable trade balance, while an increase in the inflation rate tends to have a detrimental effect. Consistency across all panel data models was observed, with the Hausman test indicating that the Random Effect model is the most suitable for this analysis.